Trimodal Sono/Photoinduced Focal Therapy for Localized Prostate Cancer: Single‐Drug‐Based Nanosensitizer under Dual‐Activation (Adv. Funct. Mater. 50/2021). (8th December 2021) - Hu, DanRong; Pan, Meng; Yang, Yun; Sun, Ao; Chen, Yu; Yuan, LiPing; Huang, KangKang; Qu, Ying; He, ChengQi; Wei, Quan; Qian, ZhiYong
Abstract : Sono/Photoinduced Therapy In article number 2104473, Zhiyong Qian and co‐workers describe the design, preparation, and evaluation of newly constructed self‐assembled nanoparticles (CS‐ss‐IR806, CSR NPs) with a redox/hyaluronidase‐responsive and mitochondria‐targeting capability to treat the early‐stage and localized prostate cancer via a photo‐/sono‐induced focal therapeutic strategy.